ANALISIS PENGARUH CITRA MEREK, DAN KUALITAS PRODUK TERHADAP MINAT BELI KONSUMEN PADA AIR MINUM KEMASAN TOYA BEJI GUWANG - Juniarta, I Made Hendra; Prawitasari, Putu Putri (LP2M Universitas Bina Bangsa, 2025)
This study aims to determine the influence of brand image and product quality partially and simultaneously on buying interest. The sample in this study is 112 consumers of Toya Beji Guwang bottled drinking water. The data analysis techniques used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, F Test and t Test. From the results of the study, it was obtained that brand image has a positive and significant effect on buying interest, product quality has a positive and significant effect on buying interest, and brand image and product quality have a significant effect on buying interest. The magnitude of the influence of independent variables on buying interest was 52.9%. The suggestion that the researcher can give is that the management of Toya Beji Guwang is expected to always build a good image, so that later consumers will always remember the Toya Beji Guwang brand when thinking about drinking water products, make more innovations in the products offered, so that later they will have features or innovations that can provide more value and are always active in implementing attractive promotions in the media, so that later consumers can get information spread.